Interleukin-1 Modulation of Human Placental Trophoblast Proliferation (Hindawi Limited, 2006)
During early pregnancy, interleukin-1 (IL-1) is mainly produced and secreted by maternal decidua. Yet, its biological function on placental cells is not well defined. In this study, we employed JAR choriocarcinoma cell line as a model of human placental trophoblast to study the effect of IL-1. Treatment with recombinant human IL-1 β resulted in significant inhibition of JAR proliferation (<mml:math alttext="$P<.05$"> P<.05 ) paralleled with increased cytotoxicity. The inhibitory effect was blocked by both IL-1 receptor antagonist (IL-1Ra) and antihuman IL-1 β monoclonal antibody. Analyzing the mode of action, IL-1 β was found to induce cell cycle arrest in the G0/G1 phase and triggered apoptotic cell death. These findings demonstrated that IL-1 regulates human trophoblast growth by induction of cell cycle delay and cell death.